ANALISIS BIAYA DAN PENDAPATAN USAHATANI CABAI MERAH KERITING DI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Susanti, Ety (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2021)
This study aims to determine 1) The cost of crop production curly red chili 2) Knowing the basic price received by farmers and Break Even Point (BEP) and R / C ratio. Farming curly red peppers give quite good gains seen from the results of this study are: the average production cost for one growing season Rp 19.663.750, - per hectare with an average production of 1.870 kilograms per hectare. The amount of basic price received by farmers for Rp. 10.515, each kilogram, while the average revenue of Rp.43.010.000,-  kilogram while farmers' income earned by Rp.23.346.250. per kilogram. From the analysis of BEP. BEP obtained by Rp.348.564 with production of 15,15 kg for the R / C ratio of 2.18 which means that every dollar spent farmers will gain acceptance of 2.18 dollars.